PENGARUH PLANT GROWTH PROMOTING RHIZOBACTERIA DAN MIKORIZA TERHADAP PENYAKIT REBAH KECAMBAH (Fusarium sp.) DAN KUALITAS BIBIT TEMBAKAU - Martinez, Tashya Angelique; Martosudiro, Mintarto; Choliq, Fery Abdul (AGRORADIX : Jurnal Ilmu Pertanian, 2024)
Tobacco plants are one of the cultivated plants that have an important role in the agricultural industry and the Indonesian economy. Tobacco cultivation in Indonesia is not free from obstacles that can cause a decrease in the quality and quantity of tobacco. A decrease in the quality and quantity of tobacco can cause a decrease in production. One of the pathogens that causes wilt in seedlings is the fungus Fusarium sp., which is one of the pathogens that causes damping-off disease in tobacco plants. The use of Plant Growth Promoting Rhizobacteria (PGPR) and Mycorrhizal biological fertilizer can be used to increase plant growth and also reduce the incidence of disease. The research was carried out in the Greenhouse and Laboratory belonging to the Agricultural Instrument Standardization Agency - Sweetener and Fiber Crops, Karangploso District, Malang City, East Java Province. The results showed that the combination treatment of PGPR and mycorrhiza (P6) was effective in suppressing disease incidence. A single mycorrhizal treatment with Fusarium inoculation (P4) was an effective treatment in influencing plant height. The combination of PGPR and mycorrhiza with and without inoculation (P6 and P5), is the best treatment because it influences seed quality and disease incidence.